In Germany, younger, better educated persons, and lower income groups are more likely to be in favor of unconditional basic income - Jule Adriaans; Stefan Liebig; Juergen Schupp (DIW Weekly Report, 2019)
Representative survey results have shown a stable approval rate for implementing unconditional basic income of between 45 and 52 percent in Germany since 2016/17. In European comparison, this approval rate is low. Younger, better educated persons, and those at risk of poverty support the concept of unconditional basic income in Germany. But these demographics are not the only factors that correlate with attitudes toward unconditional basic income: subjective justice attitudes do as well. The justice norm of equity and unconditional basic income appear to be contradictory. On the other hand, people who find that there are deficits in covering the needs of society's lower income groups tend to approve of unconditional basic income. Therefore, analyses show that attitudes toward unconditional basic income follow specific patterns and social regularities; and they were relatively stable between 2016 and 2018. As long as uncertainty predominates regarding the social costs and benefits of implementing such a basic income, the relatively high proportion of those in favor must be interpreted with care. It does not indicate that society is actually ready for reforms in this direction.
Keywords: D63; I38; H23; 330; Basic Income- Preferences; Survey